2000
DOI: 10.3354/meps192181
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a selective feeding behaviour by the blue mussel Mytilus trossulus on the assimilation of 109Cd from environmentally relevant seston matrices

Abstract: The objective of this study was to determine the influence of a selective feeding strategy on the assimilation efficiency of lo9Cd (Io9Cd-AE) by the blue mussel Mytilus trossulus. Two complementary experiments which used 5 seston matrices of different seston quality (SQ) were implemented: (1) algae labeled with Io9Cd was mixed with unlabeled silt, and (2) labeled silt was mixed with unlabeled algae. Io9Cd-A~ was determined by a dual-tracer ratio ( 1 0 9~d / 2 4 1~m ) method (DTR) and based on the ingestion rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 15 publications
1
7
0
1
Order By: Relevance
“…In fact, at the 20 mg L -1 Cd exposure level the trophic transfer to oysters was~9% for Skeletonema costatum and ~ 20% for Tetraselmis suecica, whereas at the extremely high level of 200 mg L -1 it was ~5% for both species. Thus, by comparing studies, we can conclude that trophic Cd transfer in oysters mainly depends on algae species and that the exposure level appeared to be less significant which is consistent with trophic transfer studies conducted on mussel contamination (Wang and Fisher, 1996;Reinfelder et al, 1997;Arifin and Bendell-Young, 2000).…”
Section: Trophic Contamination In Oysterssupporting
confidence: 86%
“…In fact, at the 20 mg L -1 Cd exposure level the trophic transfer to oysters was~9% for Skeletonema costatum and ~ 20% for Tetraselmis suecica, whereas at the extremely high level of 200 mg L -1 it was ~5% for both species. Thus, by comparing studies, we can conclude that trophic Cd transfer in oysters mainly depends on algae species and that the exposure level appeared to be less significant which is consistent with trophic transfer studies conducted on mussel contamination (Wang and Fisher, 1996;Reinfelder et al, 1997;Arifin and Bendell-Young, 2000).…”
Section: Trophic Contamination In Oysterssupporting
confidence: 86%
“…The complex influence of the food environment on Cd assimilation in marine bivalves has been examined rather extensively. The AE of Cd in the mussel Mytilus trossulus from silt particles increased from 36% at 50 mg/L of silt to 92% with the addition of 20,000 cells/ml of the diatom T. pseudonana [39]. Chong and Wang [40] found that the presence of sediment reduced Cd assimilation from ingested diatoms by the green mussels.…”
Section: Resultsmentioning
confidence: 99%
“…An increase in food concentration from 1 to 15 mg/L during digestion resulted in a significant decrease in the AEs of metals bound with either sediments or diatoms. Therefore, concerns have been raised whether the Cd AEs determined under laboratory conditions that typically employed simplified experimental conditions are representative of those in the natural environment [39]. In addition, bivalves are highly selective filter feeders and are able to reject unwanted materials as pseudofeces.…”
Section: Resultsmentioning
confidence: 99%
“…Particulate sources of Mn should be available as bivalves accumulate metal in their tissues from the organic and inorganic components of their diet, actively through digestive processes, and passively through desorption (Arifin and Bendell-Young, 2000). However, the peak of (Mn/Ca) shell cannot be simply explained by the bimodal pattern of total Mn p variations.…”
Section: Phytoplankton Blooms As a Source Of Bioavailable Mn?mentioning
confidence: 99%